PENGARUH PEMBERIAN JUS BUAH BIT (BETA VULGARIS L) TERHADAP KADAR HEMOGLOBIN PADA REMAJA PUTRI DENGAN ANEMIA DI SMA NEGERI 1 TALANGPADANG TAHUN 2024 - Dijah Hadijah, Erna Wati (Universitas Aisyah Pringsewu, 2024)
The prevalence of anemia in Indonesia among teenagers aged 15-24 years is 32%, or it isestimated that 3-4 out of a total of 10 teenagers suffer from anemia. Data from Lampung provinceshows that 24.8% of adolescents experienced anemia in 2018, in Tanggamus district 8.7% in 2023.Anemia in adolescent girls has an impact on decreased physical work capacity, reproductive physiology, impaired growth and decreased cognitive function. 100 grams of beetroot contains 34%folic acid, 7.4% iron, which play an important role in the formation of red blood cells in the body. Theaim of this research was to determine the effect of giving beetroot (Beta vulgaris L) juice onhemoglobin levels in adolescent girls suffering from anemia at SMA N 1 Talangpadang in 2024.This research method is a quasi-experimental research, non-equivalent control groupdesign. Sampling used purposive sampling. The population in this study were young women who weredivided into an intervention group and a control group, each consisting of 18 people. This researchwas carried out at SMA N 1 Talangpadang. The intervention given beet juice + Fe to the interventiongroup and Fe to the control group was carried out for 7 days. Statistical tests use the Paired sampleT-test and the Independent T Test.The results of the study showed that there were differences in the mean hemoglobin levels inthe two groups before and after being given the intervention. In the intervention group the averagehemoglobin level was 0.8 gr/dl and in the control group the average hemoglobin level was 0.2 gr/dl.The results of the Paired T-Test analysis test in the two groups showed that there was a significantinfluence between giving Beetroot Juice + Fe and increasing hemoglobin levels with a p-value of 0.00and there was an influence between giving Fe and increasing hemoglobin levels levels with a p-valueof 0.00. The research results showed that there were differences in mean and significance theintervention group compared to the control group. It can be concluded that giving Beetroot Juice + Feis more effective in increasing hemoglobin levels in adolescent girls. Keywords: Adolescents, Anemia, Hemoglobin, Beetroot Juiceliterature: 64 (2015-2024)